Lifestyle Narratives of Young Urban Professionals - Černevičiūtė, Jūratė (Sociologija. Mintis ir veiksmas, 2008)
The article presents the data of the qualitative research (namely deep, semi-structured interview) that was performed in 2005-2006 in Vilnius city. The aim of the research was to find out what are lifestyles narratives of young urban career professionals and did the consumer culture has influence on identities and lifestyles of Yuppies. There are done comparison between Yuppie‘s lifestyles representations in USA popular media and consumer behavior textbooks and peculiarities of Vilnius Yuppies lifestyles. Also are done comparisons between business people’s representations in Lithuanian popular media and lifestyles in Vilnius Yuppie narratives. The main attention is paid to identify job, professional careers and consumer culture elements in Yuppie‘s life. The findings of the article represent Yuppie as more career seekers than conspicuous consumption practitioners or consumer lifestyles leaders, which main identities and values are realized in professional jobs.